2016
DOI: 10.1007/s00344-015-9565-y
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of an MYB-Related Gene FvMYB1 from Fraxinus velutina Increases Tolerance to Salt Stress in Transgenic Tobacco

Abstract: MYB transcription factors (TFs) in plants play important roles in abiotic stress tolerance. Here, we report that an MYB-related TF gene, named FvMYB1, was isolated from the salt-tolerant tree species Fraxinus velutina Torr. The real-time PCR analysis showed that the FvMYB1 transcript increased remarkably in response to salt treatment. Subsequently, the FvMYB1 gene was transferred into the tobacco genome via the Agrobacterium-mediated approach. PCR and Southern blot verified that the FvMYB1 gene had been expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 52 publications
1
13
0
1
Order By: Relevance
“…GO analyses showed 10 TFs investigated here belong to the category of salt stress response genes, in which 8/10 of genes are MYB TFs, such as Glyma.12G104800 , Glyma.16G073000 , Glyma.01G107500 , Glyma.15G236400 , Glyma.06G097100 . This is consistent with previous studies that MYB TFs have been known to regulate salt stress response in plants (Yang et al, 2012; Cui et al, 2013; Li et al, 2016; Wei et al, 2017). Notably, the fold changes of some TFs were significantly higher than control plants ( Supplementary Table 3 ).…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…GO analyses showed 10 TFs investigated here belong to the category of salt stress response genes, in which 8/10 of genes are MYB TFs, such as Glyma.12G104800 , Glyma.16G073000 , Glyma.01G107500 , Glyma.15G236400 , Glyma.06G097100 . This is consistent with previous studies that MYB TFs have been known to regulate salt stress response in plants (Yang et al, 2012; Cui et al, 2013; Li et al, 2016; Wei et al, 2017). Notably, the fold changes of some TFs were significantly higher than control plants ( Supplementary Table 3 ).…”
Section: Resultssupporting
confidence: 94%
“…It has been reported that the REF6 protein, also known as JMJ12, can specifically demethylate H3K27me3 at its target gene loci to active gene expression (Lu et al, 2011). The REF6 mutants cause the ectopic accumulation of H3K27me3 at hundreds of genes and a number of defective developmental phenotypes (Yu et al, 2008; Cui et al, 2016; Li et al, 2016). ELF6 identified as an H3K27me2/3-specific demethylase closely related to REF6 was rquired for removal of H3K27me3 from the Flowering Locus C ( FLC ) locus in developing embryos in vernalized plants (Crevillen et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…MYB-related genes are the second largest member of the MYB gene family. Genes from this subfamily have diverse functions and play an important role in plant growth and stress responses, such as cell morphogenesis, secondary metabolism, organ morphogenesis, chloroplast development, leaf senescence, response to phosphate starvation and tolerance to cold, drought and salt (Dubos et al, 2010;Li et al, 2016;Yin et al, 2017;Park et al, 2018;Sun et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is reported that under stress, the expression levels NtDREB, NtRD29A (response to dehydration), NtERD10C were significantly up-regulated in transgenic tobacco of a FvMYB1 gene from Fraxinus velutina (Li et al, 2016). The increased gene expressions of stress-related genes in ZmNAGK transgenic tobaccos indicated there are different targets downstream NO to improve drought stress tolerance.…”
Section: Discussionmentioning
confidence: 99%